2010
DOI: 10.1186/1741-7007-8-33
|View full text |Cite
|
Sign up to set email alerts
|

The lethal giant larvaetumour suppressor mutation requires dMyc oncoprotein to promote clonal malignancy

Abstract: BackgroundNeoplastic overgrowth depends on the cooperation of several mutations ultimately leading to major rearrangements in cellular behaviour. Precancerous cells are often removed by cell death from normal tissues in the early steps of the tumourigenic process, but the molecules responsible for such a fundamental safeguard process remain in part elusive. With the aim to investigate the molecular crosstalk occurring between precancerous and normal cells in vivo, we took advantage of the clonal analysis metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
147
1

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(158 citation statements)
references
References 55 publications
7
147
1
Order By: Relevance
“…Similar effects are observed for lgl − and dlg − clones, although they may not be eliminated very efficiently (11,14,15). Thus, the presence of wild-type cells prevents scrib − , lgl − , and dlg − cells from manifesting their tumorigenic potential (2)(3)(4)(5)(6)(7)(11)(12)(13)(14)(15). Several groups have shown that the JNK stress-response pathway is activated in scrib − clones, leading to engulfment and death or extrusion of mutant cells from the epithelium (2-4, 6, 11, 16).…”
supporting
confidence: 60%
See 4 more Smart Citations
“…Similar effects are observed for lgl − and dlg − clones, although they may not be eliminated very efficiently (11,14,15). Thus, the presence of wild-type cells prevents scrib − , lgl − , and dlg − cells from manifesting their tumorigenic potential (2)(3)(4)(5)(6)(7)(11)(12)(13)(14)(15). Several groups have shown that the JNK stress-response pathway is activated in scrib − clones, leading to engulfment and death or extrusion of mutant cells from the epithelium (2-4, 6, 11, 16).…”
supporting
confidence: 60%
“…When scrib − cells are produced in patches (clones) of mutant cells that are surrounded by normal cells, they do not hyperproliferate, remain small, and eventually are eliminated (2)(3)(4)(5)(6)(7)(11)(12)(13). Similar effects are observed for lgl − and dlg − clones, although they may not be eliminated very efficiently (11,14,15). Thus, the presence of wild-type cells prevents scrib − , lgl − , and dlg − cells from manifesting their tumorigenic potential (2)(3)(4)(5)(6)(7)(11)(12)(13)(14)(15).…”
supporting
confidence: 48%
See 3 more Smart Citations